PENGARUH MOTIVASI TERHADAP PRESTASI BELAJAR - Ahmad Badwi (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Motive is something that resides in the individual who encourages to do something to achieve a goal or impulse that makes someone do an activity that has a specific purpose. While learning achievement is the result achieved by someone after making learning changes, both at school and outside of school. Generating motivation in several ways, namely; understanding benefits, setting goals, creating a comfortable atmosphere, getting advice or suggestions from others in learning, getting positive suggestions from others, accepting motivation from the right motivator, avoiding things that can weaken motivation, strengthening self-suggestion, completing various facilities needed to support learning activities, and instilling awareness that learning is an activity that can be classified as worship. Motivation and learning are two things that influence each other. Learning is a change in behavior that is relatively permanent and potentially occurs as a result of reinforcement based on the goal of achieving certain goals. While motivation is one of the important factors that influence learning and learning achievement. So that the higher the motivation you have, the more active your motivation will be and the learning frequency will increase.